Designing an investment map and building a geographical database for investment projects in Baghdad Governorate - Khazal Abdul-Adheem, Wassan; Ghazi Abdul-lateef, Makki (Al-Adab Journal, 2020)
The research dealt with the concept of geographic information systems and the stages of building a geographical database and preparing it for investment projects in Baghdad Governorate, designing and creating a digital investment map and getting acquainted with the number of completed investment projects in the province by type and administrative units and their job classification and indicating their geographical distribution and identifying the factors that contribute to showing this variation as it passes The process of creating the investment map with a set of stages according to the steps of building the map in geographic information systems, as the research shows the geographical and sectoral distribution of investment projects in Baghdad governorate according to Determinants of Ah affect and are affected by their geographical location be set up.